Doing qualitative research - Silverman, David (SAGE, 2017)
"Accessible, practical, and featuring indispensable advice, this best-selling textbook is the perfect hands-on guide for those embarking on their own research. With expert advice from the author and real-life experiences from students, this book shows readers how to go from the ideas of research to the practicalities of designing, conducting, and writing about research"--Provided by publisher.